Imunocromatografia, imunofluorescência indireta, ELISA e exame parasitológico "pós morten" no diagnóstico da leishmaniose visceral canina - Jader Rogerio Cappi Moraes (2006)
Validation of an immunoassay in serum from dogs in Brazil, in endemic regions, is its adoption by clinical professionals and the public service the control of canine visceral leishmaniasis. This study compared the results of the techniques of IFAT, ELISA, immunoassay and stool examination post-mortem samples not subjected to hemolysis, and hemolytic blood samples on filter paper soaked. To conduct the research was used in 30 serum samples from Belo Horizonte - MG, they all confirmed pair serum screening did not undergo the process of hemolysis. The immunoassay evaluated showed sensitivity and specificity for serodiagnosis of canine visceral leishmaniasis that enable its adoption in Brazil and could be used instead of IFA, serum samples without hemolysis by not showing statistically significant differences